Analisis Pengaruh Perilaku Pengemuditerhadap Efisiensi Energi pada Kendaraan Listrik Prototipe (Jurnal Teknik Mesin Mechanical Xplore, 2025)
The development of electric vehicles as a sustainable transportation alternative is rapidly advancing, driven by the need to reduce exhaust emissions and fossil fuel consumption. The efficiency of electric vehicles is not only determined by technical components such as electric motors, batteries, and control systems, but also by the driver's behavior during operation. This study aims to analyze the influence of driver behavior on energy efficiency in a prototype electric vehicle. The test was conducted within the campus environment of Universitas Mataram on a track with various conditions, including flat roads, curves, slight inclines, and speed bumps. Three drivers participated in the experiment, each completing three driving sessions with full freedom to drive without limitations set by the researcher. The results of the study show that driving behavior has a significant impact on energy consumption. Drivers with high speeds and aggressive acceleration tend to consume more energy. In contrast, drivers who adopted efficient driving techniques were able to save energy significantly. These findings confirm that driver behavior is an important factor in the design and development of energy-efficient electric vehicles.